Directions and prospects of transformation in cultural landscapes of Poland - considerations and attempts of evaluation - Myga-Piatek, Urszula (Acta Geographica Debrecina Landscape & Environment series, 2010)
The article points to several very up-to-date issues that occur in relation with the vanishing of traditional forms of land use and introduction of new, other than indigenous, management styles in Poland. Current processes of deterioration of the structure of the cultural landscapes have been discussed with regard to natural values and the historical process of land management by man. The article is a peculiar case study for quite common negative transformation of the polish countryside caused by relatively free use of the space, legal negligence, low awareness and poor identification of residents with the landscape – the countryside which loses its peculiar and typical features as the result of “mass consumption”. The text also presents positive examples of care taken for the regional landscape and lists initiatives aimed at improving the image of polish area.